Ontogenic Development of Heat Defenses in the Young Rat - Everett, James C. (My University, 1969)
Neonatal rats exposed to heat stress were studied to determine the age at which the saliva-spreading response appears, and to elucidate any other heat defenses that might exist before the response develops.
Saliva-spreading appeared on the 17th day of age, the age at which hypothalamic maturity is attained. This finding thus agrees with previous hypotheses that the hypothalamus is involved in the regulation of body temperature.
The tolerance of rats to an ambient temperature of 40 C dropped from 16 - 26 hours to 2 - 4 hours in the first 10 days of life. Three factors accounted for this change: decreased body water, increased rates of water loss, and increased metabolic rate.
Keywords: ontogenic development, heat defenses, young rat, temperature